Moderasi Kepemilikan Manajerial Terhadap Hubungan Profitabilitas, Leverage, Free Cash Flow Dan Manajemen Laba - Puspaningrum, Febriana Endah; Indriyani, Fany (IAIN Kudus, 2022)
The Purpose of this study is to see how Leverage, Return on Assets, and Free Cash Flow affect Earnings Management with Managerial Ownership as Moderation Variables in Islamic Banking in Indonesia that is registered with the OJK from 2015 to 2019. This study employs quantitative data analysis techniques such as multiple linear regression and MRA. For the period 2015-2019, this study makes use of secondary data in the form of panel data on Islamic commercial banks registered with the Financial Services Authority (OJK). The collected data is then analyzed using the Eviews 9 tool. This study's population included all Islamic commercial banks registered with the Financial Services Authority (OJK) between 2015 and 2019. Purposive sampling was used in order to obtain 12 Islamic commercial banks for the research sample, which were then selected using several criteria.According to the findings of this study, leverage, ROA, free cash flow, and managerial ownership have no effect on earnings management. The relationship between leverage, ROA, Free Cash Flow, and earnings management cannot be moderated by managerial ownership.